Foresight in the game as a determinant of the effectiveness of technical and tactical operations among experienced handball players - Lutkova, N. V.; Makarov, Y. M.; Pakholkova, N. V.; Zinoviev, N. A. (Theory and Practice of Physical Culture, 2025)
Objective of the study. The main objective of the work was to increase the effectiveness of the competitive activity of experienced handball players through the use of exercises aimed at developing the ability to anticipate game situations.